Strategi Hafalan Juz ‘Amma Santri Madrasah Diniyah Takmiliyah Baitul Azhar di Sumber Pakem - Ike Lestari; Muhammad Rusydi (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study aims to obtain a comprehensive understanding of the Juz ‘Amma memorization strategy implemented at Madrasah Diniyah Takmiliyah Baitul Azhar, evaluate its effectiveness, and examine the assessment mechanisms applied in Qur’anic learning. The research employed a qualitative field-study approach, focusing on learning activities as the primary object of investigation. Data were collected through direct observation of the learning process, in-depth interviews with the madrasah principal and teachers (ustadz/ustadzah), and documentation analysis related to the memorization program. The data were analyzed through data reduction, data presentation, and conclusion drawing to generate accurate and in-depth findings. The results indicate that the memorization program utilizes a combination of talaqqi, takrir (repetition), sima’i, and small halaqah methods. These strategies have proven effective in improving students’ memorization abilities, as reflected in increased reading fluency, better tajwid accuracy, and the achievement of memorization targets. In addition, the madrasah implements a structured and continuous evaluation system consisting of daily assessments, weekly reviews, and final examinations for each juz. The evaluation focuses on memorization fluency, recitation accuracy, and overall memorization quality. The study concludes that integrating diverse memorization methods with systematic evaluation significantly enhances the effectiveness of Qur’an memorization learning in Islamic educational institutions.